RESEARCH AND SIMULATION OF THE PROCESS OF AUTOMATIC MOTION OF A ROBOTIC SYSTEM USING THE COPPELIASIM ENVIRONMENT - Kovtun А.А.; Kerimbayev Н.Н; Metelev Я.В (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The use of various robotic systems is a radical restructuring not only of the industrial sphere, it implies a different attitude to thinking processes, the development of new systems in different subject areas that require new knowledge. The most effective is learning with specific motivation and an exciting form of acquiring new knowledge. The article presents a study and modeling of the process of automatic movement of a robotic system using the CoppeliaSim environment. This system is most acceptable in the conditions of remote holding of competitions in robotics. The article analyzes the use of the CoppeliaSim modeling environment, reveals its positive aspects. The authors presented the development of a robot project in a simulation environment, which assumes knowledge in the fields of design, programming, understanding of the essence of physical processes and can be recommended for organizing competitions at various levels.